The “blacksmith” and the “queen”. Freedom and divine providence in Giambattista Vico - Caporali, Riccardo (2018)
This paper aims to show that Vico cannot be considered an orthodox-catholic thinker of liber arbitrium indifferentiae. Being distinct from sacred history (that of the Jews), secular history can be openly and unapologetically investigated. The “new science” investigates the laws, constants, and regularities of the “common nature of nations” and does so neither appealing to God’s interventions nor to any idea of human will as unconditioned and transparent. On these grounds, providence is the “unexpected” logic of events, the divergence between the narrow scope of human intentions and the “wider” consequences of their actions, either powerful or disastrous. Providence (the “queen”) is “ordinary help” and leaves it up to man (the “blacksmith”) the burden to understand the meaning and aims of his own actions.